The Effects of Hedgerows Shading on Soil Temperature and Gravimetric Soil Water Content - Lešnik, Tina; Kraner Šumenjak, Tadeja; Muršec, Mateja (Agricultura Scientia, 2023)
This study sets out to examine the effects of hedgerow shading on soil physical properties, specifically soil gravimetric water content and soil temperature. Analyses of both soil parameters were conducted at two locations with different shade proportion. The aim of the study was to address the links between hedgerow shading and basic physical soil properties which could be significant both for agricultural production and for ecological processes in agroecosystems. At both locations, soil samples and measurements were taken at different distances from hedgerow and in different time intervals. Diurnal shading variation at certain distances from the hedgerow on Location 1 and 2 was calculated with the software toll for Arboriculturists. At Location 1 shading is consistently high throughout the year, ranging from 76 to 100%. In contrast, shading at Location 2 varies from 1 to 25%. The results reveal that hedgerows at Location 1, do not have a statistically significant impact on gravimetric soil water content and soil temperature across the entire plot surface. Additionally, the percentage of shading is only marginally decreases with distance. Conversely, Location 2 exhibits an increase in soil temperature and a slight but (non-significant) decrease in soil gravimetric watercontent as the distance from the hedgerow increases., The total mean shading at Location 2 is considerably lower compared to Location 1, and the shading percentage declines more at the distance from the hedgerow increases. Overall, lower soil temperatures and higher gravimetric soil water content where observed at the more shaded Location 1. The research outcomes are helpful in agricultural production planning as well as in the evaluation of hedgerows for the needs of agricultural policy.
Keywords: soil water content; soil temperature; hedgerow; sunlight